MANAGING SHIFTING FISHERIES RESOURCES - Ryan, Charlotte; Rifai, Husen; Feng, Anne; O'Hara, Nicole; Saawant, Swapnil (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2019)
The unprecedented rate of climate change and over-exploitation of resources has had a significant impact on ecosystems around the globe. In particular, the oceanic realm has encountered multiple changes to ecosystem condition, food web dynamics and habitat constructs. Many marine species have been driven to shift their geographical range in reaction to reaching their physiological limits causing severe metabolic stress. This includes key fishery targets, such as pelagic and carnivorous fish, that supply many nations with their primary or secondary protein source. The shift also spurs an array of political and economic consequences due to the need for fisheries to follow or target different fish stocks that are no longer in their exclusive economic zone or legal fishing waters. For this reason, and many other logistical and financial reasons, management strategies have struggled to maintain and sustain fish stocks around the globe. This paper will look at a Northeast Atlantic mackerel case study; compare and analyse the implications of shifting fish stocks; and illustrate difficulties related to managing the fisheries who target these stocks. Furthermore, the authors will highlight the need for a combination of a global strategies and smaller-scale ecosystem approaches in fisheries management, to be able to sufficiently sustain fisheries and thus future food security, during a time of climatic change.